How people with type 2 diabetes in Kuwait manage the condition: A thematic analysis and conceptual framework - Zainab Meer; Ebaa Al-Ozairi; Sruthi Ranganathan; Genevie Fernandes; Jay Patel (PLoS ONE, 2025)
Background Type 2 diabetes is a growing non-communicable disease burden across the Eastern Mediterranean region, particularly in Kuwait. The methods that patients adopt to manage the condition following diagnosis is poorly understood. This study aimed to explore these methods using a qualitative approach, and develop a conceptual framework characterising the phases that patients transition through. Methods This was a qualitative, thematic evaluation of a grounded theory methodology investigating the methods that patients with type 2 diabetes employ to manage their condition. Qualitative coding of semi-structured interview transcripts with 22 patients, over three phases: initial, focused and theoretical, enabled categorical themes and phases to be identified. The findings were synthesised into a conceptual framework that represented the transitional journey. Results The development of conceptual framework revealed five transitional categorical phases that characterised the journey: (1) experiencing unusual symptoms; (2) accepting the diagnosis; (3) adopting management strategies; (4) adherence and relapse; and (5) adaptation. Conclusion In Kuwait, patients with type 2 diabetes appear to transition through relatively predictable stages in learning to manage their condition. Clinical consideration of this transition could improve the quality of diabetes care provision for these patients.